2018
DOI: 10.21839/jaar.2018.v3i5.233
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological advances for climate change adaptation and mitigation in the case of goat production – A review

Abstract: Climate change influences goat production directly and indirectly thru its effect on reducing the quality and quantity of feed resources, and increasing spatial and temporal distribution of infectious diseases. The advances of biotechnology now a day’s opened an avenue to improve the nutritive value and digestibility of fibrous feeds by using biological methods (e.g., white rot fungi) and through recombinant DNA engineering techniques. Moreover, supplementation of probiotics, enzymes, antibiotics and organic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Zhang et al (2017) reported that those diseases related factors which could be affected by climate change include, the molecular biology of pathogens, vectors, zoological factors, farming practices, and the establishment of a new microenvironment. For instance, variations in seasonal rainfall distribution and specific weather conditions could cause the outbreak of certain diseases such as anthrax, bluetongue virus, facial eczema, rift valley fever, and tse tse flies which causes trypanosomiasis in ruminants (Tesema et al, 2018).…”
Section: Health and Wellbeingmentioning
confidence: 99%
See 4 more Smart Citations
“…Zhang et al (2017) reported that those diseases related factors which could be affected by climate change include, the molecular biology of pathogens, vectors, zoological factors, farming practices, and the establishment of a new microenvironment. For instance, variations in seasonal rainfall distribution and specific weather conditions could cause the outbreak of certain diseases such as anthrax, bluetongue virus, facial eczema, rift valley fever, and tse tse flies which causes trypanosomiasis in ruminants (Tesema et al, 2018).…”
Section: Health and Wellbeingmentioning
confidence: 99%
“…Droughts in Ethiopia in the 1980s and 1990s has resulted in 49% of herd losses under communal land use, while drought of the 1990s caused, 57% of the cattle mortality under ranch management (Tiruneh and Tegene, 2018). Moreover, bush encroachment and population pressure led to the diminishing availability of good pasture are among various reasons for the loss of genetic diversity (Tiruneh and Tegene, 2018;Tesema et al, 2018;and Naod et al, 2020).…”
Section: Genetic Diversitymentioning
confidence: 99%
See 3 more Smart Citations